Bioremediation of Phenanthrene, Chrysene, and Benzo[a]pyrene by Fungi Screened from Nature - Tony Hadibrata; Sanro Tachibana (Journal of Mathematical and Fundamental Sciences, 2009)
Laccase of Polyporus sp. S133 was able to oxidize most of the 3 different rings amount polycyclic aromatic hydrocarbons (PAHs) tested. Phenanthrene was removed by 89% followed by chrysene and benzo[a]pyrene which were oxidized by 66 and 55%, respectively. Addition of 1-hydroxybenzotriazole (HBT) to the reaction mixture increased oxidation of PAHs, especially phenanthrene was almost completely removed from the reaction mixture. Oxidation of chrysene and benzo[a]anthracene increased 12 and 10% with the mediator to 78 and 65% in the presence of HBT. PAH-quinones as oxidation products were formed from all PAH to different extents. A part of PAH was polymerized in the laccase/mediator system to products of weight-average molecular weight (MW). The correlation of the ionization potentials of PAH with the oxidation of these compounds is limited to the alternating PAH.